Bentham on asceticism and tyranny. Issue 1 (2nd January 2019) - Koh, Tsin Yen
ABSTRACT: In the late 1810s, Jeremy Bentham wrote a set of texts entitled Not Paul, But Jesus, arguing against the religious authority of St. Paul, and the principle of asceticism he propagated. This paper argues that Bentham's critique of the principle of asceticism was not only or primarily a religious one, but a political one. Bentham objected to the principle of asceticism because it could be used to provide practical and ideological support for tyranny. The principle of asceticism, as a principle which repudiated common pleasures, provided a 'cloak' for tyranny, in giving rulers a reason to establish laws which penetrated further into the everyday activities of men and women (than would have been justified under the principle of utility), and so enabled them to increase their power over their subjects. The principle of asceticism also enabled rulers to create the conditions of fear and social isolation, which encouraged obedience to their laws. The Not Paul texts and related writings can be read as an extended argument against the principle of asceticism as a political principle, and as a defence of common pleasures.